2012
DOI: 10.1002/pi.4408
|View full text |Cite
|
Sign up to set email alerts
|

Which is more effective for protein adsorption: surface roughness, surface wettability or swelling? Case study of polyurethane films prepared from castor oil and poly(ethylene glycol)

Abstract: In order to investigate the effects of surface roughness, surface wettability and swelling on protein adsorption, polyurethane films were prepared from castor oil (CO) and poly(ethylene glycol)‐3000 (PEG) using one‐shot bulk polymerization. Hexamethylene diisocyanate and 1,4‐butanediol were used as isocyanate and chain extender, respectively. The hydrophilicity of the polyurethane films was adjusted by varying the ratio of CO to PEG. The surface of the polyurethane films was treated using plasma polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…All samples exhibit characteristic polyurethane peaks in their FTIR spectra (Figure ). As mentioned in experimental part, the absence of the absorbance at around 2265 cm −1 for the final product indicated consuming of isocyanates and formation of polyurethane . The disappearance of the absorption peak at 3464 cm −1 , assigned to the hydroxyl group, confirmed that all hydroxyl groups were consumed in the reaction.…”
Section: Resultsmentioning
confidence: 53%
“…All samples exhibit characteristic polyurethane peaks in their FTIR spectra (Figure ). As mentioned in experimental part, the absence of the absorbance at around 2265 cm −1 for the final product indicated consuming of isocyanates and formation of polyurethane . The disappearance of the absorption peak at 3464 cm −1 , assigned to the hydroxyl group, confirmed that all hydroxyl groups were consumed in the reaction.…”
Section: Resultsmentioning
confidence: 53%
“…19 Roughness of surfaces also play a critical role in adhesion of proteins. 21, 22 It has been found to be an important factor at the nanometer scale for both fibrinogen and bovine serum albumin attachment. 21 Increasing random roughness increases the adhesion of proteins to surfaces of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness and surface physicochemical properties (among them wettability) of the biomaterial are interrelated with the protein adsorption phenomenon. 9,10,11 The water adsorption to the implant surface depends on the charge density of the surface which is strongly influenced by its nanoscale roughness. 12,13 These factors have the major contribution in defining the implant surface-to-blood interactions as well as influencing the cell adhesion and, consequently, their growth and differentiation.…”
Section: Introductionmentioning
confidence: 99%